Self-Realization In Paulo Coelho’s Veronica Decides To Die - Agnes Milleniawati Hibur; Yoseph Bavo Agung Prasaja (Proceeding of Undergraduate Conference on Literature, Linguistic, and Cultural Studies, 2022)
This thesis discusses the self-realization experienced by the characters in Paulo Coelho’s Veronica Decides to Die. Self-realization is a process of forming the complete personality of an individual, in the sense that an individual will undergo a realization about his life towards an awareness that will shape his personality. The problem that he raises in this research is about the forms of individual personality that will be related to the process of realization, the factors that can affect the process of realization, as well as the implications that are obtained as a result of the achievement of individual self-realization. The objectives of the research are to identify and analyze forms, factors, and implications of self-realization. In the process of analyzing this problem, the researcher uses three theories, The first theory is Analytical psychology by Carl Jung to analyze individual personality forms, Self-Actualization by Carl Rogers to analyze the factors that influence self-realization, and Hierarchy of needs by Maslow. to analyze the implications of the self- realization process of each individual. The research method used is the researcher used a psychological approach. The results of the analysis show that four characters experience self-realization in the novel, namely, Veronica, Zedka, Eduard, and Mary. They each have their reasons and get their realization targets. They were met in Villete, a mental hospital where they could carry out the realization process.